1995
DOI: 10.1097/00000542-199502000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Cerebral Blood Flow during Anesthesia with Isoflurane or Halothane in Humans 

Abstract: There is a difference in the human rCBF distribution between halothane and isoflurane with higher relative flows in subcortical regions during isoflurane anesthesia. However, despite this redistribution, isoflurane anesthesia resulted in a lower mean CBFxenon than did anesthesia with halothane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 31 publications
1
25
1
1
Order By: Relevance
“…Previous study in the baboon has reported that isoflurane resulted in dose-related MAP decrease, cerebral metabolism depression, and biphasic CBF response (CBF decreases at low isoflurane doses (<1%) but increase in high doses (~1.4%)) [11]. Evident CBF increase was observed in thalamus and basal ganglia and pons of humans anesthetized with 1 MAC isoflurane but not in cortex [10, 14]. With high dose (2.0% or more) isoflurane, previous study in dogs has found that under 2.8% isoflurane, CBF was increased significantly in cerebrum, medulla, cerebellum, caudate and CBF autoregulation was eliminated compared to 1.4% [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study in the baboon has reported that isoflurane resulted in dose-related MAP decrease, cerebral metabolism depression, and biphasic CBF response (CBF decreases at low isoflurane doses (<1%) but increase in high doses (~1.4%)) [11]. Evident CBF increase was observed in thalamus and basal ganglia and pons of humans anesthetized with 1 MAC isoflurane but not in cortex [10, 14]. With high dose (2.0% or more) isoflurane, previous study in dogs has found that under 2.8% isoflurane, CBF was increased significantly in cerebrum, medulla, cerebellum, caudate and CBF autoregulation was eliminated compared to 1.4% [27].…”
Section: Discussionmentioning
confidence: 99%
“…The dose-dependent influence of isoflurane on CBF, autoregulation, brain metabolites, brain functional performance, et al, are observed in various animal and human studies. It has been demonstrated abnormal CBF increase under mild or high dose isoflurane in non-human primates, and humans [5, 9-11, 14]. In addition, high isoflurane doses could abolish the coupling between CBF and cerebral metabolites and impair CBF autoregulation in primate and human [5, 11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Studies report a decrease in regional blood flow to brainstem, cerebellum, and thalamus, while primary sensory systems like olfaction and vision and the limbic cortex show increased perfusion (Schlünzen et al, 2004, 2006; Alkire et al, 1997; Reinstrup et al, 1995). This variability is also observed in rats as region-specific increases and decreases in glucose utilization and cerebral blood flow (Ori et al, 1986; Lenz et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Vascular effects of isoflurane in a heterogeneous vascular bed, as in SAH, may be variable and counterproductive. Even in healthy humans, isoflurane may cause a redistribution of flow, increasing flow in subcortical regions (5). It is possible that in pathologic circumstances, such as in SAH, vasodilatation induced by isoflurane may occur in intact, rather than in damaged intracranial vessels, as in case of vasospasm.…”
mentioning
confidence: 99%
“…While much is understood in terms of risk stratification for its occurrence (3), and meta-analyses suggest some value for prophylactic therapeutic interventions (e.g., amiodarone, β-blockers, sotalol, magnesium, and atrial pacing) (4,5), there has been only modest progress in the prevention of postoperative AF, and no prospective evaluation involving interruption of the RAAS. However, numerous compelling leads of research evidence have existed, prospective and retrospective, to collectively support the thesis that a reasonably selected (angiotensin-converting enzyme) inhibitor or mineralocorticoid blocker prophylaxis regimen could protect against the occurrence of postoperative AF.…”
mentioning
confidence: 99%